Agricultura familiar e alimentação escolar nos grandes municípios paulistas: análise das características institucionais em redes políticas - Bueno, Gabriel (2020)
The Federal Law 11.947 of 2009 establishes - in its article 14 - that states and counties, when carrying out actions of the National School Feeding Program (PNAE), must spend at least 30% of the resources received from the National Fund for the Development of Education (FNDE) buying products from family farming. Such regulation aims at forming a policy network, defined as a set of relatively stable relationships between various actors that have an interdependent nature in sharing resources. The logic of the networks advances in explaining the coordination mechanisms between the actors in public policies. It is argued that networks gradually emerge because actors begin to interact and when they exist for a longer period, institutional characteristics such as patterns of interaction, patterns of perceptions and rules emerge. The research aims to analyze the institutional characteristics in political networks structured from the implementation of article 14 of Law 11,947 / 2009 in twenty large cities in São Paulo. From the clusters analysis by the Ward method with 106 family farmers' organizations, it was possible identify four groups of family organizations with different patterns of interaction (intensity and variety) with the counties studied. The variables used in the statistical test were: sales volume (VV), number of counties served (NM) and total years that the organization participated in the Program (TA). A multiple case study was also carried out based on the application of a questionnaire with a family organization from each group observed in the statistical test. The results show that, despite the different patterns of interaction between family organizations in different clusters, some perceptions about the main problems in the process of purchasing products from family farming for school meals are similar. The perceptions about the rules are connected to the actor, as they vary according to the actor's situation in the network and how he feels affected by the compliance (or not) of these rules.